Flying cars and boring companies: Interrogating the feasibility of the transport futures of tech executives. (February 2022) - Marx, Paris; Manaugh, Kevin
Highlights: Transport futures from the tech industry require more critical assessment. Flying cars and underground tunnels have been proposed as transport futures. Both futures fail to contend with inequities of an auto-oriented transport system. Alternative transport futures not limited by automobility realism are necessary. Abstract: Powerful actors in the technology industry are increasingly turning their attention to various aspects of the future of human societies, promising the futures they desire will bring benefits to the whole of the human population. However, there is reason to be skeptical of those assertions, especially in relation to the transport futures advocated by tech executives. Using the theoretical perspective of automobility realism, this paper interrogates two tech-driven transport futures: Uber's vision of skies buzzing with helicopter-like flying cars and Elon Musk's desire for layers upon layers of automobile tunnels below city streets. The paper performs a critical analysis which focuses on how executives describe their proposed solutions and how they are represented in documents and images released by the companies; the degree to which they challenge or exist within a transportation system built around automobiles; and whether the solutions proposed can realistically address the harms and inequities of the existing system. The paper ends with a reflection on how imagining alternative transport futures could open up different possibilities.